2009
DOI: 10.1021/jp9047924
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ethene Adsorption on Clean and C-Contaminated Cu(410)

Abstract: As recently established (J. Am. Chem. Soc. 2008, 130, 12552), ethene adsorption on Cu(410) occurs both molecularly and dissociatively, the latter resulting in carbon contamination of the Surface. Here we report on the coverage-dependent dynamics of C(2)H(4) adsorption on clean and carbon-contaminated Cu(410). For the bare surface, the initial sticking probability has a very weak dependence on kinetic energy and is almost independent of angle of incidence. Molecular adsorption is in both cases precursor-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 22 publications
2
24
1
Order By: Relevance
“…6(b). This conclusion is different from the previous assumption that ethylene dehydrogenate on Cu(410) should be through the long-bridge state (σ-lb-ss) [16,17]. Notice that the unimportance of the long-bridge intermediate state is consistent with the extremely low barrier from this state to the more DOI:10.1063/1674-0068/31/cjcp1805120 c ⃝2018 Chinese Physical Society stable π-s-v configuration.…”
Section: B Further Dehydrogenation Steps and The Kinetic Networkcontrasting
confidence: 66%
See 3 more Smart Citations
“…6(b). This conclusion is different from the previous assumption that ethylene dehydrogenate on Cu(410) should be through the long-bridge state (σ-lb-ss) [16,17]. Notice that the unimportance of the long-bridge intermediate state is consistent with the extremely low barrier from this state to the more DOI:10.1063/1674-0068/31/cjcp1805120 c ⃝2018 Chinese Physical Society stable π-s-v configuration.…”
Section: B Further Dehydrogenation Steps and The Kinetic Networkcontrasting
confidence: 66%
“…Recently, the adsorption of ethylene on Cu(410) has been intensively investigated [14][15][16]. At low temperature and low coverage, ethylene binds with the Cu(410) surface with a π-bonded configuration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known from previous work that π-bonded ethene adsorbs reversibly at low Miller index Cu surfaces [6][7][8]. However, recent studies have shown [9][10][11] that on Cu(410) not only di-σ bonding, but also complete dehydrogenation occurs at low crystal temperature (T ). The carbon resulting from dissociation decorates the step edges and deactivates them.…”
Section: Introductionmentioning
confidence: 99%